THE PRACTICAL-AMBIGUOUS SUBJECT (COPING IN AND WITH THE WORLD). - Sanders, Mark (Review Journal of Political Philosophy, 2009)
An essay is presented on practical-ambiguous subject for philosophy. It states that the subject pertains to man and his importance to philosophical discourse. It cites the cognitive concept of Rene Descartes on man's mental act, and the ideas of Michael Foucault and Jacques Derrida on the death of the subject. It also notes that the subject has an inextricable connection with the world.